SAT0018 Identification of new epistatic interactions with the HLA region in the genetic etiology of psoriasis and psoriatic arthritis. (23rd January 2014) - Marsal, S.; Hernanz, J.M.; Cañete, J.D.; Fonseca, E.; Ferrandiz, C.; Unamuno, P.; Puig, L.; Fernández-Sueiro, J.L.; Sanmartí, R.; Rodriguez, J.; Gratacόs, J.; Dauden, E.; et al.
Abstract : Background: Psoriatic Arthritis (PsA) is a complex disease and is present in ∼11% in patients with Psoriasis (Ps). Recently, Genomewide Association Studies (GWAS) have expanded the number of risk loci for Ps in >20 new loci. Two of these genes, ERAP-1 and HLA-C, have been shown to interact epistatically in the risk to develop Ps. Objectives: We have studied the presence of new genetic interactions between Ps risk lci with the HLA region in Purely cutaneous Psoriasis (PsC) and PsA. Methods: Within each Ps risk locus (n=31), the SNP having the highest statistical evidence was selected. The 31 SNPs were genotyped using Taqman technology in a cohort of n=955 PsA, 1, 050 PsC and 1, 497 hypernormal controls of the Spanish population. The presence of statistically significant gene-gene interactions was performed using a logistic regression model with three parameters to determine the presence of interaction at the allelic level. Results: We replicated the previously described interaction of HLA-C and ERAP1 in the PsC cohort but not in the PsA cohort. We identified, for the first time, a significative epistatic association between HLA-C and SERPINB8 . Microarray gene expression studies on cutaneous biopsies corroborate the presence of this interaction at a functional level. In PsA, no statistically significant interactions where identified with variation at HLA-C . However, 6 of the studied genes showed a significant ( P <0.05) association with HLA-B27 positivity. Conclusions: The present study has identified new genetic interactions associated with the risk to develop PsC and PsA. The functional study of these interactions will improve our knowledge of the biological basis of these complex diseases. Disclosure of Interest: None Declared